Build infrastructure in publishing scientific journals to benefit medical scientists - Dai, Ni; Xu, Dingyao; Zhong, Xiyao; Li, Li; Ling, Qibo; Bu, Zhaode (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
There is urgent need for medical journals to optimize their publishing processes and strategies to satisfy the huge need for medical scientists to publish their articles, and then obtain better prestige and impact in scientific and research community. These strategies include optimizing the process of peer-review, utilizing open-access publishing models actively, finding ways of saving costs and getting revenue, smartly dealing with research fraud or misconduct, maintaining sound relationship with pharmaceutical companies, and managing to provide relevant and useful information for clinical practitioners and researchers. Scientists, publishers, societies and organizations need to work together to publish internationally renowned medical journals.